Pien Tze Huang Inhibits Hypoxia-Induced Angiogenesis via HIF-1α/VEGF-A Pathway in Colorectal Cancer. (14th January 2015) - Chen, Hongwei; Feng, Jianyu; Zhang, Yuchen; Shen, Aling; Chen, Youqin; Lin, Jiumao; Lin, Wei; Sferra, Thomas J.; Peng, Jun
Abstract : Hypoxia-induced angiogenesis plays an important role in the development and metastasis of solid tumors and is highly regulated by HIF-1 α /VEGF-A pathway. Therefore, inhibiting tumor angiogenesis via suppression of HIF-1 α /VEGF-A signaling represents a promising strategy for anticancer treatment. As a traditional Chinese medicine formula, Pien Tze Huang (PZH) has long been used as a folk remedy for cancer in China and Southeast Asia. Previously, we reported that PZH inhibits colorectal cancer (CRC) growth both in vivo and in vitro. To elucidate the antitumor mechanisms of PZH, in the present study we used human umbilical vein endothelial cells (HUVEC) and colorectal carcinoma HCT-8 cells to evaluate the effects of PZH on hypoxia-induced angiogenesis and investigated the underlying molecular mechanisms. We found that PZH could inhibit hypoxia-induced migration and tube formation of HUVEC cells in a dose-dependent manner, although the low concentrations of PZH had no effect on HUVEC viability. Moreover, PZH inhibited hypoxia-induced activation of HIF-1 α signaling and the expression of VEGF-A and/or VEGFR2 in both HCT-8 and HUVEC cells. Collectively, our findings suggest that PZH can inhibit hypoxia-induced tumor angiogenesis via suppression of HIF-1 α /VEGF-A pathway.